Emerging single‐cell technologies in immunology. Issue 1 (23rd April 2015) - Herderschee, Jacobus; Fenwick, Craig; Pantaleo, Giuseppe; Roger, Thierry; Calandra, Thierry
Abstract : Review of the rationale, potential, and working principles of single cell technologies for profiling host immune responses. Abstract : During evolution, the immune system has diversified to protect the host from the extremely wide array of possible pathogens. Until recently, immune responses were dissected by use of global approaches and bulk tools, averaging responses across samples and potentially missing particular contributions of individual cells. This is a strongly limiting factor, considering that initial immune responses are likely to be triggered by a restricted number of cells at the vanguard of host defenses. The development of novel, single‐cell technologies is a major innovation offering great promise for basic and translational immunology with the potential to overcome some of the limitations of traditional research tools, such as polychromatic flow cytometry or microscopy‐based methods. At the transcriptional level, much progress has been made in the fields of microfluidics and single‐cell RNA sequencing. At the protein level, mass cytometry already allows the analysis of twice as many parameters as flow cytometry. In this review, we explore the basis and outcome of immune‐cell diversity, how genetically identical cells become functionally different, and the consequences for the exploration of host‐immune defense responses. We will highlight the advantages, trade‐offs, and potential pitfalls of emerging, single‐cell‐based technologies and how they provide unprecedented detail of immune responses.